GABA, Glutamate, and NAA Levels in the Deep Cerebellar Nuclei of Essential Tremor Patients - Buijink, Arthur W. G.; Prent, Naomi; Puts, Nicolaas A.; Schrantee, Anouk; Potters, Wouter V.; van Rootselaar, Anne-Fleur (Frontiers in Neurology, 2021)
Background: Essential tremor is among the commonly observed movement disorders in clinical practice, however the exact pathophysiological mechanisms underlying tremor are unknown. It has been suggested that Purkinje cell alterations play a causal factor in tremorgenesis. Altered levels of inhibitory (GABA) and excitatory (glutamate+glutamine, Glx) neurotransmitters could be markers for Purkinje cell alterations. We hypothesize that GABA and Glx levels in the dentate nuclei could be differentially altered in patients responsive to either anticonvulsants or β-adrenergic blockers. Methods: In this explorative study in patients with essential tremor, we measured gamma-aminobutyric acid (GABA) and glutamate+glutamine (Glx) levels in the dentate nucleus region using 1H-magnetic resonance spectroscopy (MRS) in seven patients using propranolol, five patients using anticonvulsants, and eight healthy controls. Results: There were no group differences with respect to GABA+/Cr, Glx/Cr, NAA/Cr and GABA+/Glx ratios. There was no correlation with tremor severity. Discussion: Our results are in line with previously published studies; however, additional studies on a larger number of patients are warranted to confirm these findings. Furthermore medication-subgroups did not exhibit differences with respect to GABA+/Cr, Glx/Cr, NAA/Cr and GABA+/Glx ratios. A recent study, of similar size, found an inverse association between tremor severity and the GABA+/Glx ratio in the cerebellum of essential tremor patients. We were unable to replicate these findings. The field of tremor research is plagued by heterogeneous results, and we would caution against drawing firm conclusions based on pilot studies.